Il futuro della scuola (FrancoAngeli, 2023)
This volume presents an internship path implemented at the Free University of Bozen-Bolzano, as a part of the Hons. Bachelor of Science in Primary Education. The project is the result of an experiential journey closely connected with the mission and activities of Multilab, a laboratory dedicated to scientific, ecological, cultural, and social education. The aim of de Lab is to promote excellence and creating interdependencies within and beyond the Faculty of Education. In the 21st century, The future of the school, demands teachers proficient in new languages and environments characterized by the digital dimension. The internship, particularly the indirect internship, serves as the space where students have the opportunity to practice these skills through communication, production, and sharing of artifacts. Their experience and reflections are later collected in an e-portfolio, a digital product that chronicles the progressive process of each student’s growth and development. The volume is the result of the collaborative efforts of the internship coordinators, the director of the degree program, and the successive deans of the Faculty between 2017- 2021. Together they designed an innovative path within Italian university landscape, focusing on teacher education pathways.